Tracing the Rash: Diaphragmatic Paralysis Following Cervical Herpes Zoster - Yasuhiro Kano (American Journal of Medicine Open)
An 80-year-old man presented with a two-day history of anorexia and decreased daily activity. A physical examination revealed an erythematous, crusted, vesicular eruption distributed along the C3-C5 dermatome. Chest x-ray and computed tomography during inspiration and expiration demonstrated an elevation of the left hemidiaphragm with almost no movement of the left diaphragm during respiration. These findings were consistent with left diaphragmatic paralysis due to cervical herpes zoster. As a rare type of segmental motor paresis, cervical herpes zoster can cause phrenic nerve paralysis because the phrenic nerve originates in the anterior horn of the C3 to C5 roots. Diaphragmatic paralysis results in diminished vital capacity and can lead to a decline in exercise tolerance or daily activity, especially in elderly patients.